Integarate Muji's character into new Chinese packaging design for better value and aesthetic appearance - Hang, Wang; Alli, Hassan; Shaahbudin, Shahrul Azman; Raja Ahmad Effendi, Raja Ahmad Azmeer (Human Resource Management Academic Research Society, 2023)
In the evolving realm of product packaging, the intersection of minimalistic MUJI design principles and traditional Chinese aesthetics offers a promising avenue for exploration. This study delves into the potential of integrating MUJI's design elements into Chinese packaging to enhance its value and appearance. Rooted in a detailed analysis of MUJI's unique design philosophy and the rich traditions of Chinese packaging aesthetics, this research employs a quantitative approach using semi-structured questionnaires. Primary findings suggest that certain MUJI design characteristics can be seamlessly integrated into Chinese packaging, leading to a harmonious blend of simplicity and cultural richness. Through a comparative analysis, this study identifies opportunities for elevating the design value of Chinese packaging, thereby providing invaluable insights for designers and manufacturers aiming to combine the best of both worlds. The implications of this study pave the way for future innovations in the packaging industry, redefining the way products are presented and perceived in the market.